Peran TQM dan Teknologi dalam peningkatan kualitas: Studi kasus pada toko asih - Nurhaliza, Dwi (Maliki Interdisciplinary Journal, 2025)
In establishing a business, the owner must pay attention to the services that consumers and employees receicve to facilitate operational efficiency in improving service quality by developing real tehcnology including easy access to product information, ease of technology by using computers by utilizing the role of Total Quality Management (TQM). This research uses a qualitative approach using information gethering techniques throught case studies based on the results of interviews obtained. The result shows a lack of knowledge of information technology at Asih Shop. Where Asih Shop still does not use tehnology optimally in the businnes operational process so that business ineffectiveness often occurs due to incompatibility with the income obtained. Meanwhile, Total Quality Management (TQM) at Asih Shope is in accordance with standard the role of Total Quality Management (TQM) in resolving problems at Shope Asih. In resolving problems found in This businnes, Asih shop has done it based on sharia principles and resolved the problems throught deliberation by finding the middle point of the problem.